Pengembangan Video Pembelajaran IPA Terpadu pada Tema Konservasi Gajah Berkarakter Peduli Lingkungan - Yudiyanto Yudiyanto; Nasrul Hakim; Dwi Kurnia Hayati; Hifni Septina Carolina (Journal of Natural Science and Integration, 2020)
This study aims to develop integrated science learning videos with environmental characteristics. The theme of the learning video is elephant conservation in Way Kambas National Park. The development of this learning video is expected to increase student learning motivation and in its implementation it will develop a caring character for the environment in students. This research uses the Research and Development method which includes survey methods in the process of developing learning videos. The results showed that the material expert validation was twice with the results a score of 91%, including in the very valid category. The validation of media experts was a score was 92% which was included in the very valid category. The results of the small group trial for 10 students obtained a score of 91% including in the very good category, the results of the large group trial for 30 students obtained a score of 93% including in the very good category. Based on all aspects of the assessment of the development of instructional videos carried out by material experts and media experts and trials with students, it can be concluded that the integrated science video learning product on the theme of elephant conservation with environmental care characteristics developed is suitable for use in the learning process.Keyword: environmental care, elephant conservation, learning videoABSTRAK.Tujuan Penelitian ini adalah untuk mengembangkan video pembelajaran IPA terpadu yang memuat karakter peduli lingkungan. Tema video pembelajaran yang dikembangkan adalah konservasi gajah di Taman Nasional Way Kambas. Pengembangan video pembelajaran ini diharapkan mampu meningkatkan motivasi belajar siswa dan pada implementasinya akan menumbuhkan karakter siswa untuk peduli lingkungan. Metode yang digunakan dalam penelitian ini adalah Research and Development yang memuat metode survei dalam proses pengembangan video pembelajaran. Hasil penelitian menunjukkan bahwa validasi ahli materi dilakukan 2 kali dengan diperoleh skor 91% termasuk dalam kategori sangat valid. Validasi ahli media dilakukan sebanyak dua kali dan diperoleh skor akhir 92% termasuk dalam kategori sangat valid. Hasil ujicoba kelompok kecil kepada 10 orang siswa diperoleh skor 91% yang tergolong dalam kategori sangat baik, hasil uji coba kelompok besar kepada 30 orang siswa diperoleh skor 93% termasuk dalam kategori sangat baik. Berdasarkan seluruh aspek penilaian terhadap pengembangan video  pembelajaran yang dilakukan oleh ahli materi dan ahli media serta uji coba kepada siswa dapat disimpulkan bahwa produk videopembelajaran IPA terpadu pada tema konservasi gajah berkarakter peduli lingkungan  yang dikembangkan layak digunakan dalam proses pembelajaran.Kata kunci: peduli lingkungan, konservasi gajah, video pembelajaran